Membaca Max Havelaar dan Berjuta-juta dari Deli; Mengkonstruksi Realitas Indonesia Pascakolonial - Saifur Rohman (HISKI, 2009)
This paper will discuss how a contemporary work of literature is coherent with a work of the past, corresponding with facts of the past and in the end seeks to construct present day Indonesia. The work discussed is Berjuta-juta dari Deli (2006) (BD) by Emil W. Aulia, which was strongly infuenced by Max Havelaar atau Lelang Kopi di Maskapai Dagang Belanda (1860) (MH). The influence can be seen in the story-telling technique, stereotyping of characters, plot and theme of colonialişm. The thing is, MH was written in colonial time and the writer was directly involved, while BD was written by an author who lives in postcolonial time about a century later. his difference resulted in the ways of interpreting the colonial society. The method applied is Russian formalism which puts an importance in sequence and plot. The analyzing technique is the historical hermeneutics of Hans-Georg Gadamer. Based on the postcolonial theory, heuristic analysis is employed to uncover the mask of present day Indonesian character. The result is, the construction of Indonesia today is actually the shadow of/infiuenced/constructed by yesterday's Indonesia The shaping of today's character can not be separated from the conception that existed in the time of the Dutch occupation. This shaping has three stages. First, Indonesian man is metaphorically characterized as animal (buffalo) Second, since the communicative character is buffalo, the media of communication are orders and physical punishments. Third, if not buffalo, the Indonesian man is a believer of false hopes spread by agents of neo-colonialism. Considering this result, we need to shape the nation's character with things that can free us from the three mentioned stages of interpretation, minderlijk, colonial mentality and the miserable condition of the Netherlands Indie Truly, we had been free before.